Simulation of planet formation in circumstellar disks - Markelova, T.V.; Snytnikov, V.N. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2012)
A numerical model of dynamics for a massive self-gravitating protoplanetary is proposed with consideration of inelastic pair collisions of particles. In the conducted computing experiments with ring structures in a disk, it is shown that the mass range change of particles occurs with the reproduction of the ring structure. It is found that the released thermal energy in bodies is maximal for bodies of small mass. This work was supported by the Integration project SB RAS (coordinator Acad. Mikhailenko B.G.) and the Presidium programs RAS NN 21, 22, 28.